Activity of Trovafloxacin (with or without Ampicillin-Sulbactam) against Enterococci in an In Vitro Dynamic Model of Infection - Zinner, Stephen H. (American Society for Microbiology, 1998)
Antibiotic-resistant enterococci are being increasingly identified as causal agents of infection. Trovafloxacin is a new fluoronaphthyridone with enhanced activity against gram-positive cocci and variable activity reported against Enterococcus spp. Twenty-one strains of vancomycin-resistant Enterococcus faecium and two strains of Enterococcus faecalis (one vancomycin resistant) were studied at an initial inoculum of 10(6) CFU/ml in time-kill assays with trovafloxacin (3 mg/liter), ampicillin-sulbactam (100/50 mg/liter), and the combination. Six strains of E. faecium (five vancomycin resistant) also were studied in an in vitro two-compartment dynamic model that mimics human pharmacokinetics with trovafloxacin simulated at 300 mg every 12 h (q12h), ampicillin-sulbactam at 2/1 g q6h, and the combination. Peripheral compartments were sampled q2h for 30 h for bacterial counts. Trovafloxacin MICs ranged from 0.5 to 32 mg/liter, and the nine strains of vancomycin-resistant E. faecium for which MICs were ≤2 mg/liter were more likely to show a reduction of 2 log units or more in viable counts in time-kill assays than were strains for which MICs were higher. Synergism with ampicillin-sulbactam was found for only one strain (trovafloxacin MIC, 16 mg/liter). Similar results were obtained in the pharmacokinetic model, with 2- to 4-log-unit reductions in viable bacteria for trovafloxacin-susceptible strains. Although no convincing evidence of synergism was found, ampicillin-sulbactam in combination minimized late bacterial regrowth of two trovafloxacin-susceptible strains. These data suggest that this high dose of trovafloxacin (with or without ampicillin-sulbactam) might be useful against strains of vancomycin-resistant E. faecium for which MICs were ≤2 mg/liter.